Grozljiva zgovornost tišine: slikarstvo Luca Tuymansa - Vignjević, Tomislav (Monitor ISH, 2008)
The art of Luc Tuymans, one of the best known contemporary painters, is marked by a highly personal approach. His paintings are mostly characterised by fragmentary, discontinued narration which isolates certain details (interiors, faces, objects .). The viewer can unravel their complex metaphorical meanings only through a close examination of their contextual connotations. This isolation of a fragment, one of the most typical proceduresin his paintings, invites comparison with Freud's concept of das Unheimliche, where a mundane fragment confronts us with an ćunheimlichć background narrative, be it Nayism, the colonial past, or disease.
Keywords: Tuymans, Luc, 1958-; art of painting; slikarstvo; sodobno slikarstvo; narativnost; refleksija